2022
DOI: 10.3389/fneur.2022.889090
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics features of DSC-PWI in time dimension may provide a new chance to identify ischemic stroke

Abstract: Ischemic stroke has become a severe disease endangering human life. However, few studies have analyzed the radiomics features that are of great clinical significance for the diagnosis, treatment, and prognosis of patients with ischemic stroke. Due to sufficient cerebral blood flow information in dynamic susceptibility contrast perfusion-weighted imaging (DSC-PWI) images, this study aims to find the critical features hidden in DSC-PWI images to characterize hypoperfusion areas (HA) and normal areas (NA). This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Other studies of some prognostic predictions have found similar results [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In these studies, we can see that the performance of radiomics based on different types of images (MRI, CT and CTA) gives good results in predicting prognostic factors such as the mRS scale after AIS or the presence of disability after AIS.…”
Section: Prognostic Predictionsupporting
confidence: 69%
“…Other studies of some prognostic predictions have found similar results [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In these studies, we can see that the performance of radiomics based on different types of images (MRI, CT and CTA) gives good results in predicting prognostic factors such as the mRS scale after AIS or the presence of disability after AIS.…”
Section: Prognostic Predictionsupporting
confidence: 69%
“…By measuring the first pass of contrast, PWI provides quantitative information about CBF, cerebral blood volume (CBV), and mean transit time (MTT). PWI is beneficial in the evaluation of acute ischemic strokes as well ( 33 ). It can distinguish between regions of hypoperfusion and regions of completed infarction, aiding in the selection of patients who may benefit from reperfusion therapies.…”
Section: Mrimentioning
confidence: 99%
“…The training dataset consisted of 159 LGG patients with pre-operative MRI images and 1p/19q status proven by biopsy. They were identified within the LGG-1p19q Deletion dataset [15,26,27] on The Cancer Imaging Archive (TCIA).…”
Section: Datamentioning
confidence: 99%
“…In [158], the deep learning model was trained to detect the stroke area on non-contrast CT scans. In [159], the model was trained to distinguish between hyperperfusion areas from normal ones. In [160], primary and secondary hemorrhages were classified.…”
Section: Strokementioning
confidence: 99%